Home country supportiveness/unfavorableness and outward foreign direct investment from China - Gaur, Ajai S; Ma, Xufei; Ding, Zhujun (Journal of International Business Studies, 2018)
What drives the outward foreign direct investments (OFDIs) by emerging market firms (EMFs)? Drawing on a strategy tripod framework, this article proposes a theoretical model to predict OFDI by EMFs from China. Specifically, we use institution- and industry-based views to examine two facets of home country environment, namely, the supportiveness from home government and unfavorableness from home industry, as important determinants of OFDI, and compare the relative strength of these effects. Further, we use the resource-based view to argue that the effect of the home country environment is contingent on the international experience portfolios of EMFs.